Specific features of kinetics of thermal transformation of organic matter in Bazhenov and Domanik source rocks based on results of pyrolysis gas chromatography - Svetlana V. Mozhegova; Roman S. Gerasimov; Irina L. Paizanskaya; Anna A. Alferova; Elizaveta M. Kravchenko (Записки Горного института)
Pyrolysis of organic matter with subsequent analysis of hydrocarbon composition of the resulting products allows obtaining multicomponent distribution spectra of the generation potential by the activation energies of reactions of kerogen transformation into hydrocarbons. Configuration of the spectra depends on the structure of kerogen and is individual for each type of organic matter. Studies of kerogen kinetics showed that the distribution of activation energies is unique for each oil source rocks. The kinetic model of thermal decomposition of kerogen of the same type, for example, marine planktonic (type II), can differ significantly in different sedimentary basins due to the multivariate relationship of chemical bonds and their reaction energy threshold. The developed method for calculating multicomponent kinetic spectra (four-component models are used) based on results of pyrolysis gas chromatography allows obtaining one of the most important elements of modelling the history of oil and gas generation in geological basins. Kinetic parameters of organic matter of oil and gas source rocks influence the onset time of generation and directly reflect differences in the composition and structure of different types of kerogens. The results of determining the kinetic parameters of two high-carbon source rocks occurring across the territory of three oil and gas basins are shown. Generation and updating of the data of kinetic models of certain oil and gas source rocks will increase the reliability of forecasting oil and gas potential using the basin modelling method.